Biotex Natto+: A Polyherbal Nutraceutical Targeted For Cardiovascular Health. - Rebello Leroy; Polineni Sahithi; Chepyala Sreesudha (Asian Journal of Pharmaceutical Research and Development, 2026)
Objective(s): To assess clinical, preclinical, regulatory and safety evidence on the efficacy of nattokinase in cardiovascular health and the rationale for the combination formulation of Biotex Natto+ (nattokinase 250 mg, bromelain 250 mg, standardised nanocurcumin 50 mg). Data Sources: Relevant published studies were retrieved from PubMed, Scopus and Google Scholar. Study Selection: Published clinical trials, systematic reviews, meta-analyses and preclinical studies with methodological rigour investigating the effect of nattokinase and/or combination therapy on blood pressure, fibrinolytic activity, haemostatic factors, atherosclerosis and carotid intima-media thickness were selected. Summary of Contents: Cardiovascular diseases are the leading cause of death worldwide despite the availability of effective pharmacological interventions. Nattokinase is a 27.7 kDa subtilisin-like serine protease from natto that has been extensively investigated as a fibrinolytic nutraceutical. Clinical studies provide preliminary evidence on the antihypertensive, fibrinolytic, anti-inflammatory and anti-atherosclerotic effects of nattokinase. Moderate decreases in systolic and diastolic blood pressures and plasma fibrinogen, coagulation factors VII and VIII were reported alongside improvement in carotid intima-media thickness. Bromelain and curcumin nanoparticles may contribute additional cardioprotective effects, although evidence on the formulated product is indirect. Conclusion: Nattokinase possesses cardioprotective properties and further clinical studies are warranted to establish the efficacy of the formulated product, Biotex Natto+.